Arithmetic-Grammar: The Development of Learning Model in Tenses - Shofiyuddin, Muh.; Sutama, Sutama; Prayitno, Harun Joko; Andriyani, Santi (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2025)
This study aims to discuss about learning tenses through arithmetic-grammar model. It was conducted with some steps: (1) preliminary stage, (2) field research, (3) tenses conception development, (4) expert validation, (5) product revision, (6) testing, (7) final products, (8) users’ response. It was conducted in English education department and the respondents are both the students and the lecturer. The preliminary research and field research showed that the way and material complexity of learning are the problem mostly make students get difficulties to master tenses. Thus, it needs to build an effective learning model with more interesting way and simple material, through arithmetic based grammar. After the conducting this study, the results show that the product of tenses conception through arithmetic-grammar has a Good criteria with users’ response average 46.48. Product usefulness aspects in improving grammar skills gained an average 4.88 and 4.54 for writing. It can be concluded that integrated arithmetic-grammar model is a good way for learning tenses and effective to improve students’ tenses mastery.